“Is your commute really making you fat?”: The causal effect of commuting distance on height-adjusted weight - Olga Lorenz; Laszlo Goerke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper explores the causal relationship between commuting distance and height-adjusted weight (BMI) in Germany, using micro-level data for the period 2004 – 2012. In contrast to previous papers, we find no evidence that longer commutes are associated with a higher BMI. The non-existence of a relationship between BMI and commuting distance prevails when physical activity and eating habits are adjusted for.
Keywords: D00; I12; R41; 330